VALIDITAS DAN RELIABILITAS INSTRUMEN ALAT UKUR SIT UP BERBASIS TEKNOLOGI DIGITAL - muhamad sazeli rifki; Fiky Farma (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
This study aims to create a sit-up measurement tool based on digital technology that can provide the effectiveness and efficiency of testors and testees. firstly validated by an electrical expert and a test and measurement expert. Continue the small group test of 10 people and a large group of 20 people. Based on the results of the study showed that the Digital Technology-based Sit Up Test Measure was categorized as